ENO1 couples HDAC1 to regulate histone lactylation and gene transcription - Guijin Zhai; Fei Zhao; Yuhan Wang; Zixin Jiang; Yanan Li; Zilong Fan; Wei Zheng; Yanpu Han; Jianji Zhang; Yong Zang; Kai Zhang (Proceedings of the National Academy of Sciences, 2026)
Histone deacetylases (HDACs) regulate transcription and catalyze deacetylation predominantly within canonical transcriptional complexes. Nevertheless, the mechanistic role of other HDAC-associated proteins in orchestrating this process remains incompletely understood. To systematically decode endogenous HDAC interactomes in living cells, we developed BimPL, a heterobifunctional molecule-enabled proximity labeling strategy. Leveraging BimPL and quantitative proteomics, we robustly captured established HDAC complexes and identified putative interactors, including glycolytic enzyme enolase-1 (ENO1). Importantly, we uncover that ENO1 translocates into the nucleus and interacts with HDAC1 at chromatin, which in turn blunts the activity of HDAC1 through locally generated phosphoenolpyruvate (PEP). Consequently, the ENO1–HDAC1 coupling promotes histone lysine lactylation (Kla), which drives transcriptional reprogramming of oncogenes in hepatic malignancies. Our study establishes BimPL as a versatile tool for mapping endogenous protein interactomes and reveals a metabolic enzyme-orchestrated HDAC regulatory mechanism for histone lactylation, highlighting ENO1’s moonlighting function in epigenetic reprogramming.